Metagenomic insights into bacterial communities in eco-enzymes and their microbial diversity and abundance - TITTA NOVIANTI; HENNY SARASWATI; H. HAFSAH; SEPRIANTO SEPRIANTO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Novianti T, Saraswati H, Hafsah H, Seprianto. 2025. Metagenomic insights into bacterial communities in eco-enzymes and their microbial diversity and abundance. Biodiversitas 26: 2157-2166. The aim of microbial diversity analysis of eco-enzymes is to optimize their benefits in various fields, such as for use in disinfectants, household cleaning agents, liquid fertilizers, and more. Metagenomic profiling is an effective method of analyzing microbial diversity that involves determining the nucleotide sequences of microbial DNA and allows the identification and taxonomic classification of certain bacteria. In this study, metagenomic analysis was carried out on eco-enzymes derived from mangosteen peel, orange peel, and a mixture of 16S rRNA gene primers. We visualized the amplification results using electrophoresis to confirm the length of the DNA base band obtained. We then sequenced the Polymerase Chain Reaction (PCR) products using MinKNOW software (version 23.04.5; Oxford Nanopore Technologies, Oxford-UK). The bioinformatics metagenomic analysis included chronological visualization, Sankey phylogenetic analysis, heat map graphing, and Venn diagram visualization. The study's results showed that in the mangosteen peel eco-enzyme there were bacteria from 7 different phyla. The results of the alpha-diversity index analysis showed the highest value of 2,050 compared to other samples. However, the abundance of each species was lower than that in the other samples. In contrast, the orange peel eco-enzyme had only one bacterial phylum, and the mixed vegetable eco-enzyme had two bacterial phyla. This finding indicates that mangosteen peel eco-enzyme has the most abundant bacterial diversity from different phyla than orange peel eco-enzyme and mix-vegetables, which may cause diversity in the enzyme content produced.